2022
DOI: 10.1093/ckj/sfac237
|View full text |Cite
|
Sign up to set email alerts
|

The Many Faces of NELL1 MN

Abstract: Neural tissue encoding protein with EGF-like repeats (NELL1) is a recently discovered target antigen in membranous nephropathy (MN). The initial study showed that most cases of NELL1-MN had no underlying disease associations, i.e. most cases of NELL1-MN were classified as primary MN. Subsequently, NELL1-MN has been found in the setting of various diseases. These include NELL1-MN associated with malignancy, drugs, infections, autoimmune disease, hematopoietic stem cell transplant, de novo MN in a kidney transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…This nding is consistent with the data from the Human Protein Atlas 17 and supports the previously reported possibility of breast cancer as a source of NELL1 antigen. 6 Our case depicts the di culty in interpreting NELL1-MN, reinforcing the ndings reported in the recent review by Sethi et al 5 NELL1-MN is associated with almost all causes of secondary MN. Therefore, we cannot conclude which underlying diseases have affected MN development in our case, even after establishing the diagnosis of NELL1-MN.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…This nding is consistent with the data from the Human Protein Atlas 17 and supports the previously reported possibility of breast cancer as a source of NELL1 antigen. 6 Our case depicts the di culty in interpreting NELL1-MN, reinforcing the ndings reported in the recent review by Sethi et al 5 NELL1-MN is associated with almost all causes of secondary MN. Therefore, we cannot conclude which underlying diseases have affected MN development in our case, even after establishing the diagnosis of NELL1-MN.…”
Section: Discussionsupporting
confidence: 85%
“…Several small studies suggested that MN might be induced by chronic HCV infection. 14 Additionally, Sethi et al 5 recently reported that NELL1-MN was detected in 25% of hepatitis B-associated MN cases and has also been detected in a patient with active hepatitis C. Thus, active HCV infection may have affected the development of NELL1-MN in our case.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“… 1 , 2 , 3 In 2019, 2 groups identified the NELL1 podocyte antigen in a subset of MN with distinct histologic and immunologic features, namely segmental or incomplete glomerular capillary loop involvement with predominant IgG1 staining. 4 , 5 NELL1 MN has also been identified in association with thiol-containing medications, namely lipoic acid, 6 , 7 bucillamine, 8 and tiopronin 9 ; traditional indigenous medications, including those with high mercury content 10 ; and with underlying conditions, including malignancy, 5 infections (including HIV 11 ), sarcoidosis, 12 hematopoietic stem cell transplant and graft-versus-host disease, 13 and rheumatoid arthritis. 8 …”
mentioning
confidence: 99%